Executive functioning in 6 year old children exposed to chemotherapy in utero. (December 2020) - van Gerwen, Mathilde; Vandenbroucke, Tineke; Gorissen, An-sofie; van Grotel, Martine; van den Heuvel-Eibrink, Marry; Verwaaijen, Emma; van der Perk, Madeleine; Van Calsteren, Kristel; van Dijk-Lokkart, Elisabeth M.; Amant, Frédéric; ,
Abstract: Background: Cancer treatment during pregnancy imposes a dilemma. Maternal advantage should be weighed against the potential impact of chemotherapy on child development. Recent studies in cancer survivors have shown that exposure to chemotherapeutic agents can have late adverse effects on cognitive functioning and executive functioning (EF). It is still unclear whether these late adverse effects also arise if a child is exposed to chemotherapy in utero. Aim: To compare the development of executive functioning in 6 year old children prenatally exposed to chemotherapy (study group) and children born to healthy women after an uncomplicated pregnancy (control group). Methods and study design: In a multicenter cohort study, the outcome on a measure of EF was compared. Study and control children were prospectively examined by means of the Behavior Rating Inventory of Executive Function (BRIEF), a health questionnaire and an intelligence test. Results: In total 37 study children and 37 matched controls were included. In the study group, 11 children (29.7%) were exposed to chemotherapy alone, 22 children (59.5%) were exposed to chemotherapy and surgery and 4 children (10.8%) were exposed to chemotherapy, surgery and radiotherapy during pregnancy. All outcome scales of the BRIEF were within normal ranges. However, a significant between-group difference in emotional control was found. Conclusion: Overall outcomes of EF were reassuring. However, children prenatally exposed to chemotherapy have weaker emotion regulation skills compared to their matched controls. The results underscore the need for long-term follow-up of these children. Highlights: Children prenatally exposed to chemotherapy do not differ in the development of executive functions at age 6. Parents of children prenatally exposed to chemotherapy reported more difficulties to modulate emotions and behavior. Follow up and surveillance of emotional development of these children is highly important.